The Presence of Cartilage Affects Femoral Rotational Alignment in Total Knee Arthroplasty - Yang, Yiming; Zeng, Xianli; Jin, Yan; Zhu, Zhemin; Tsai, Tsung-Yuan; Chen, Jiarong; Shen, Hongyuan; Li, Pingyue (Frontiers in Surgery, 2022)
Objective: To assess the difference between the posterior condylar angle (PCA) and the mechanical lateral distal femoral angle (mLDFA) in the osseous and cartilaginous contours in a non-arthritic Chinese population. Methods: Computed tomography (CT) and magnetic resonance imaging (MRI) were obtained from 83 patients with knee injuries before arthroscopy, and femur and distal femoral cartilage three-dimensional (3D) models were constructed. The 3D cartilage model was arranged to share physical space with the 3D femoral model, and then PCA and mLDFA were measured on the osseous and cartilaginous contours, respectively. The differences between the measurements with and without cartilage were evaluated. Results: The average PCA with cartilage was 2.88 ± 1.35° and without was 2.73 ± 1.34°. The difference was significant in all patients and females but not in males. The average mLDFA with cartilage was 84.73 ± 2.15° and without cartilage was 84.83 ± 2.26°, but the difference was statistically insignificant in all groups. Conclusion: PCA on the osseous and cartilaginous contours significantly differed with and without cartilage in the female group, suggesting that cartilage thickness should be considered during preoperative femoral rotational resection planning.